Impact of marketing communication and affiliate marketing strategies on marketing performance: an empirical study on online merchants in the shopee marketplace - Firmansyah, Firmansyah; Sulastri, Sulastri; Aslamia Rosa (SEAN Institute, 2024)
In recent years, online business in Indonesia has experienced rapid growth. This condition is undoubtedly supported by technological advancements and a high number of internet users. Moreover, with the change in consumer behavior leaning towards online shopping, the shift from offline to online shopping patterns has led to the closure of retail stores in Indonesia, a phenomenon also observed in several other countries. The transition from offline to online sales systems has intensified competition in the online business landscape. The fierce competition requires merchants to develop effective strategies to remain the number one choice in the hearts of consumers. By employing appropriate strategies and platforms, merchants hope to reach their target market and increase sales volume. In this context, marketing communication plays a crucial role in informing, persuading, and reminding consumers directly or indirectly about the products and brands being sold. Additionally, affiliate marketing is equally important in this strategy, promoting merchandise through online platforms and sharing profits through revenue-sharing methods. This research aims to determine the extent to which marketing communication and affiliate marketing influence the increase in sales volume. The study adopts a quantitative research approach using purposive sampling techniques. The sample consists of Shopee marketplace merchants, with data collected through the distribution of questionnaires to 100 respondents. The analysis employed is multiple linear regression, and the results show that both marketing communication and affiliate marketing have a positive and significant impact on increasing sales volume. The coefficient of determination (R Square) is 0.389, indicating that 38.9% of the variation in sales volume is influenced by marketing communication and affiliate marketing, while the remaining 61.1% is attributed to unexplored external factors in this study